Integration of sales channels on the way to omnichannel distribution of goods (Journal of Economic Research & Business Administration, 2024)
With the development of digital technologies, as well as the constant transformation of consumer behavior, there is a need to integrate sales channels that will retain existing customers and influence the emergence of the new ones. In this regard, the relevance of studying and implementing omnichannel distribution is determined as the preferred way to meet customer needs, and within which all points of interaction on various sales channels with customers are integrated and work without obstacles.The purpose of the research in the article was to determine the directions of integration of sales channels during the transition to omnichannel distribution of goods. For this purpose, a survey was conducted among 456 respondents; the survey questions were related to preferences in choosing an online and offline purchasing channel. Further, the work used methods of theoretical research, comparative analysis, and generalization to formulate conclusions and results, as well as the tool of the Job-to-be-done method. A study of customer preferences showed that consumers prefer to use elements of omnichannel distribution, but do not have such an opportunity. After that, the authors proposed a scheme for integrating online and offline sales channels. The peculiarity of this article is that the authors have adapted the tool of the Job-to-be-done approach to the topic of the research, based on it, drivers of the behavior of channel participants on the way to omnichannel sales were offered in order to determine the advantages of the proposed solutions, as well as to understand what barriers may occur when implementing changes.The theoretical significance of the article lies in the generalization of ideas about the role and significance of omnichannel distribution in the economic literature of domestic and foreign authors. The practical significance is that the results of this study will allow companies to gain insight into the customer experience to implement an integrated sales system and increase their willingness to purchase in in the conditions of omnichannel.Key words: omnichannel distribution, customer, behavior, buyer need, digital marketing.